2016
DOI: 10.1093/femsec/fiw245
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the role of the porcine intestinal yeast,Kazachstania slooffiae, in intestinal environment of weaned piglets

Abstract: Kazachstania slooffiae is a porcine intestinal yeast whose role in the intestinal environment is largely unexplored. Therefore, the impact of K. slooffiae on growth performance, intestinal microbial metabolites and the microbiota of weaned piglets was investigated in this study. Forty-eight German Landrace pigs were weaned at day 27 or 28 of life and grouped into one control and three treatment groups. During the 5-week experiment, piglets had ad libitum access to feed and water. On days 5, 6 and 7 post weanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 49 publications
0
28
0
Order By: Relevance
“…On another level, we provided evidences of the association between piglets body weight after weaning and members from the fungal and protists gut eukaryote community. A previous study with growing piglets, reported no significant effects on growth performance parameters upon oral supplementation with K. slooffiae [57]. However, a recent detailed metabolic study conducted by the same authors [58] under laboratory conditions with cultures of K. slooffiae, concluded that this yeast produces peptides and short chain fatty acids that might benefit the gut health, and provides an additional protein source that contains essential amino acids and other useful growth factors for the animal [58].…”
Section: Discussionmentioning
confidence: 94%
“…On another level, we provided evidences of the association between piglets body weight after weaning and members from the fungal and protists gut eukaryote community. A previous study with growing piglets, reported no significant effects on growth performance parameters upon oral supplementation with K. slooffiae [57]. However, a recent detailed metabolic study conducted by the same authors [58] under laboratory conditions with cultures of K. slooffiae, concluded that this yeast produces peptides and short chain fatty acids that might benefit the gut health, and provides an additional protein source that contains essential amino acids and other useful growth factors for the animal [58].…”
Section: Discussionmentioning
confidence: 94%
“…weaning). Based on their original findings, the same research group studied the effect of a K. slooffiae strain isolated from pigs' faeces on growth performance, intestinal microbial metabolites and gut microbiota (Urubschurov et al, 2016). While we acknowledge that this approach may not necessarily lead to the best potential candidates as probiotic species, and that multiple in vitro tests are advisable to determine the functionality, it is also true that this line of thought (i.e.…”
Section: Should We Choose An Indigenous or A Foreign Microorganism Asmentioning
confidence: 99%
“…Kazachstania, a species complex of Ascomycetous yeasts, has been isolated from a number of captive species, including K. heterogenica and K. pintolopesii from rodents, K. slooffiae from pigs and horses and K. bovina from cows and birds [56]. Although little is known about its functions, recent experimental studies have shown the importance of Kazachstania for the development of a healthy porcine microbiome, where Kazachstania populations support growth of SCFA-producing bacteria [57,58]. On the [59].…”
Section: Discussionmentioning
confidence: 99%